Exploration of child bullying cases and school-based anti-bullying interventions and community empowerment in Semarang City - Melawati, Lia Berta (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Background: Education plays a crucial role in shaping the success of a nation, both in academic aspects and character development. This research explores the factors contributing to bullying, encompassing individual, family, school, and social environment aspects. Methods: Using a qualitative approach through literature review, data were collected from various sources related to bullying in Indonesia, such as scientific journals, books, and official documents. The sample was purposively selected to represent the bullying conditions in Indonesia. Content analysis was used to identify patterns and trends. Findings: The findings indicate a weak correlation between age and bullying potential, highlighting the importance of a holistic approach involving the entire school community. Collaborative-based intervention methods were identified as effective intervention strategies. This study also provides insights into verbal bullying and body shaming. Conclusion: the research lies in its in-depth exploration of the bullying phenomenon among Indonesian teenagers, particularly at the junior and senior high school levels, considering the unique cultural and social context. Novelty/Originality of this Study: this research includes elementary school levels, offering a comprehensive analysis of the influence of social media and family dynamics, and providing unique insights for the development of policies and intervention programs in Indonesia.